Risk Management and Compliance Strategies for Legacy IT Infrastructure - Yurii Shevchuk (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This article examines strategies for risk management and regulatory compliance in the context of modernizing legacy IT infrastructure. The relevance of the topic arises from the growing need to integrate new technological solutions in environments characterized by limited flexibility, high maintenance costs, and technical debt—factors that contribute to operational, technical, and regulatory risks. The study analyzes the current state of legacy infrastructure, identifies key threats and vulnerabilities, and develops methodological approaches including modular migration, AI-driven analytics, the adoption of cloud technologies, and the integration of advanced security measures to ensure compliance with regulatory frameworks such as GDPR and HIPAA. The scientific novelty lies in proposing a new perspective on integrating strategic planning, change management, and modern security technologies to reduce operational costs and improve business resilience. This perspective emerged through a critical review of existing literature. The author’s hypothesis suggests that a comprehensive approach to modernizing legacy IT infrastructure—grounded in modular transition to cloud solutions and automated security monitoring—will lead to a reduction in risk and an increase in the efficiency of business processes. The findings of this study may be of interest to IT management professionals, risk and compliance officers, and researchers seeking to integrate the latest analytical methods into the evaluation and modernization of inherited IT systems. The presented material is also expected to be useful to other scholars developing theoretical models for managing complex IT environments, as well as to practitioners implementing strategies for mitigating operational and regulatory risks amid continuous technological and legal transformation.